2018
DOI: 10.1111/tid.13035
|View full text |Cite
|
Sign up to set email alerts
|

Late cytomegalovirus (CMV) infections after kidney transplantation under the preemptive strategy: Risk factors and clinical aspects

Abstract: Background Late cytomegalovirus infections (LCMV) after the cessation of prophylaxis are well described. We aimed to assess clinical and epidemiological data on late‐occurring cytomegalovirus (CMV) infections in the absence of CMV prophylaxis in a cohort of kidney transplant patients. Methods In a cohort of kidney transplant recipients not employing CMV‐specific prophylaxis, patients with CMV infections occurring after 6 months of transplantation were compared to patients with CMV infections diagnosed within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In immunocompetent individuals, CMV remains asymptomatic but has the potential to reactivate when the immune system is compromised [19]. In immunocompromised patients, primary CMV infection causes severe complications such as pyrexia, viremic-septicemia, pneumonitis and in rare cases CMV induced immunosuppression [23,24]. CMV may also disseminate to the gastrointestinal tract and cause ulcerations.…”
Section: Adult Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In immunocompetent individuals, CMV remains asymptomatic but has the potential to reactivate when the immune system is compromised [19]. In immunocompromised patients, primary CMV infection causes severe complications such as pyrexia, viremic-septicemia, pneumonitis and in rare cases CMV induced immunosuppression [23,24]. CMV may also disseminate to the gastrointestinal tract and cause ulcerations.…”
Section: Adult Transmissionmentioning
confidence: 99%
“…Active CMV in the eye primarily infects vascular endothelial cells followed by retinal pigment epithelial cells in the retina causing viral cytopathic effect and subsequent retinal necrosis, as characterized in CMVR [25]. The large viral genome of CMV quickly translocates to the infected cell nucleus and starts production of viral progeny in a lytic lifecycle [24,25,32]. Viral progeny then bud out of the infected cell to infect neighboring cells and repeat the process.…”
Section: Pathogenesis Of CMV Retinitismentioning
confidence: 99%
“…We read with great interest the recently published article entitled "Late cytomegalovirus (CMV) infections after kidney transplantation under the preemptive strategy: Risk factors and clinical aspects" by of G. Ono et al 1 The authors found that these late-onset CMV infections were associated with a higher rate of invasive disease and graft loss than earlier infections occurring in the first 6 months following the transplantation. In a previous article, we found that lateonset CMV diseases were associated with a lower DNAemia peak, a shorter CMV therapy and fewer recurrences than early-onset diseases because of a faster anti-CMV immune response.…”
Section: Late Vs Early-onset CMV Infections In Kidney Transplantationmentioning
confidence: 99%
“…Therefore, in general, prophylactic treatment for CMV infection is administered to recipients in the high and moderate risk groups [6]. Over recent years, as the CMV PCR diagnostic method has started to be used to rapidly and correctly reveal CMV viral replication, a preemptive treatment strategy has come to prominence [7,8]. Prophylactic treatment is antiviral therapy applied for 3-6 months from 10 days after transplantation [9].…”
mentioning
confidence: 99%
“…These two approaches are similar in respect of CMV infection but studies have shown differences in respect of side-effects [7,[9][10][11][12]. However, these studies have been conducted with limited numbers of patients, and there has been variability in the follow-up periods and the antivirals used.…”
mentioning
confidence: 99%